Enhancing English Learning Motivation in Early Childhood Through Singing Activities in Handio Village - Nasution, Enni Efrida; Harahap, Rijal Allamah; Harahap, Siti Layla Safriyyah; Harahap, Rizky Sakinah (PT. LITERASI SAINS NUSANTARA, 2025)
English language learning for early childhood in Handio Village has increasingly been introduced since the preschool (PAUD) level. This demand has led parents to enroll their children in schools where English is used as a medium of instruction. As a foreign language in Indonesia, English is gradually being introduced at the early childhood education (PAUD) level. Children aged 0–6 years are in their golden age, a critical period in human development that significantly influences their future growth. Therefore, all aspects of language should be introduced before this phase ends. English is now being introduced at the kindergarten level. To effectively teach English, appropriate learning methods must be employed to spark students’ interest and motivation in using English in fun, engaging learning activities—both in spoken and written forms—in ways that are fluent and socially contextual. This research aims to explore the implementation of English learning at the early childhood education (PAUD) level in Handio Village. Data collection was carried out through interviews to obtain direct verbal information. Among the preschools in Handio Village, one kindergarten (TK) was selected as the research site. From the data obtained, this TK has already integrated English learning into its teaching and learning process.